2001
DOI: 10.1254/jjp.86.189
|View full text |Cite
|
Sign up to set email alerts
|

Affinity of Serotonin Receptor Antagonists and Agonists to Recombinant and Native α1-Adrenoceptor Subtypes

Abstract: ABSTRACT-Binding affinities of serotonin (5-HT)-receptor antagonists and agonists at human recombinant a1-adrenoceptor subtypes (a 1a-, a1b-and a1d-subtypes) were examined and compared with the functional affinities obtained in rat caudal artery (a1A-subtype), dog carotid artery (a1B-subtype) and rat thoracic aorta (=1D-subtype). Most of the 5-HT-receptor antagonists and agonists tested showed relatively high affinity to three a 1-adrenoceptor subtypes. The highest affinity close to 1 nM was seen for in bindi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
1
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(31 citation statements)
references
References 27 publications
1
28
1
1
Order By: Relevance
“…9 On the other hand, the same authors demonstrated that the selective a 1a ADR antagonist REC 15=2841 failed to inhibit CN mediated ICP responses in rats or dogs at doses 10 -30 times higher than the dose of spiperone used in the present study. Although we are not able to completely rule out an a-ADR antagonist action for the effect of spiperone on m-CPP induced ICP in the present study, it is interesting to note that ketanserin is comparable to spiperone in terms of affinity and potency as an a 1 -ADR antagonist 23,25 but failed to significantly reduce the m-CPP induced ICP response. Naloxone, yohimbine and 8-OHDPAT have differential effects on erection elicited in different experimental models and were employed here in order to gain some insight into the relevance of the m-CPP induced ICP response to other models of erection.…”
Section: Discussioncontrasting
confidence: 66%
See 1 more Smart Citation
“…9 On the other hand, the same authors demonstrated that the selective a 1a ADR antagonist REC 15=2841 failed to inhibit CN mediated ICP responses in rats or dogs at doses 10 -30 times higher than the dose of spiperone used in the present study. Although we are not able to completely rule out an a-ADR antagonist action for the effect of spiperone on m-CPP induced ICP in the present study, it is interesting to note that ketanserin is comparable to spiperone in terms of affinity and potency as an a 1 -ADR antagonist 23,25 but failed to significantly reduce the m-CPP induced ICP response. Naloxone, yohimbine and 8-OHDPAT have differential effects on erection elicited in different experimental models and were employed here in order to gain some insight into the relevance of the m-CPP induced ICP response to other models of erection.…”
Section: Discussioncontrasting
confidence: 66%
“…10 Spiperone exhibits selectivity for the a 1a ADR subtype. 22,23 Prazosin, a non-selective a 1 -2 antagonist, is often m-CPP induced intracavernous pressure responses ES Hayes and PG Adaikan used to induce erection or enhance erection produced by other agents. 24 However, in anesthetized rats and dogs prazosin tends to reduce ICP elicited by stimulation of the CN but this effect is not clearly dose-dependent and, differs between species.…”
Section: Discussionmentioning
confidence: 99%
“…In light of the present results and considering that these drugs bind to both adrenergic and serotonergic receptors (Yoshio et al 2001), it now seems likely that these serotonergic drugs also block constitutive activity at ␣ 1 receptors. Constitutively active 5-HT 2 receptors and ␣ 1 adrenergic receptors likely play an equally important role in facilitating spasms, because they contribute equally to PICs and blocking both these receptors essentially eliminates the PICs (Harvey et al 2006b).…”
Section: Constitutive Activity In ␣ 1a Receptors Contribute To Recovementioning
confidence: 56%
“…A similar two-site, high-and low-affinity profile of BMY 7378 was calculated for specific 125 I-HEAT binding sites on these same cells, which confirms mature expression of the ␣ 1D -AR and validates our ␣ 1A -AR subtype observation using 5-MU. Although ␣ 1B -AR expression could be represented as part of the low-affinity binding population for both 5-MU and BMY 7378, previous reports have shown consistent 3-to 4-fold lower binding affinities of BMY 7378 for both recombinant and endogenously expressed ␣ 1A -AR subtypes compared with the ␣ 1B -AR (Yoshio et al, 2001). The extremely low-affinity population (K iL ) identified by BMY 7378 in our human macrophage system correlates well with the calculated BMY 7378 value for ␣ 1A -AR subtypes in the previous report (Yoshio et al, 2001).…”
Section: Discussionmentioning
confidence: 86%